Simulation of structural transformations in copper nanoparticles under collision; Наносистемы: физика, химия, математика; Т. 2, № 2 - Smolin A. Yu. Alexey Yurievich; Roman N. V.; Zolnikov K. P.; Psakhie S. G. Sergey Grigorievich; Kedrinskii V. K. (2011, 2011)
Заглавие с экрана